Your sons and strangers : lesser-known british writers in the spanish civil war - Melia, Paul Joseph (2013)
Ralph Fox, Christopher Caudwell, John Cornford, Ralph Bates, Esmond Romilly, Julian Bell and Tom Wintringham were politically motivated Britons who felt compelled to help Spain’s effort to combat Fascism. Apart from Julian Bell they were all Marxists who, at least in their published writing, hoped for a Communist revolution and expressed decidedly orthodox Communist opinions. They were dismissive of left-wing alternatives and portrayed the Soviet Union as evidence of the correctness of Marx’s philosophy. Spanish political life in the early to mid-1930s was much more turbulent than in Britain, as shown in the novels of Ralph Bates, an émigré in Spain, and Ramon J. Sender. Verbal and physical conflict was shown to be possible at any time, while groups like the Communists and Anarchists had an influence in Spain that did not exist in Britain. The political and social diversity and frequent incompatibility that Bates, Sender and other Spanish writers around this time depicted make the Civil War look inevitable. In this dissertation I also look at the compulsion these writers felt to risk their lives in Spain, which remains somewhat enigmatic. The threat of Fascism, and in particular of Fascism menacing Britain, was probably enough to make these Marxists appreciate the relative benefits of a bourgeois democracy. Their experiences of the war suggest that they were not prepared or probably even psychologically suitable for enduring such an ordeal and the fact that they were overseas under foreign command added to their difficulties.